2019
DOI: 10.3389/fphar.2019.01367
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Properties of Ranolazine: Inhibition of Atrial Fibrillation Associated TASK-1 Potassium Channels

Abstract: Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and one of the major causes of cardiovascular morbidity and mortality. Despite good progress within the past years, safe and effective treatment of AF remains an unmet clinical need. The anti-anginal agent ranolazine has been shown to exhibit antiarrhythmic properties via mainly late I Na and I Kr blockade. This results in prolongation of the atrial action potential duration (APD) and effective refractory period (ERP) with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 70 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…Homodimeric K 2P 2.1 (TREK-1) channels are inhibited by the anticonvulsant drugs valproate, gabapentin and carbamazepine [ 102 ] by the antidepressants like fluoxetine, paroxetine, citalopram or escitalopram ( Table 3 ) [ 96 , 102 ], and the antipsychotics haloperidol or clozapine [ 101 ]. While some of these interactions would only be relevant at supratherapeutic plasma levels, others already have an impact in the physiological range [ 141 ].…”
Section: K 2p 21 (Trek-1)mentioning
confidence: 99%
“…Homodimeric K 2P 2.1 (TREK-1) channels are inhibited by the anticonvulsant drugs valproate, gabapentin and carbamazepine [ 102 ] by the antidepressants like fluoxetine, paroxetine, citalopram or escitalopram ( Table 3 ) [ 96 , 102 ], and the antipsychotics haloperidol or clozapine [ 101 ]. While some of these interactions would only be relevant at supratherapeutic plasma levels, others already have an impact in the physiological range [ 141 ].…”
Section: K 2p 21 (Trek-1)mentioning
confidence: 99%
“…Ranolazine’s effect on the molecular electrophysiology has been investigated in previous studies. Ranolazine acts as a multi-ion-channel blocker, blocking late and peak I Na , I Kr [ 3 ], and as recently shown, the nearly atrial specific two-pore domain potassium channel TASK-1 [ 4 ]. Sossalla et al [ 19 ] demonstrated altered sodium channel kinetics with increased late I Na (I NaL ) in atrial appendages from patients with AF and furthermore showed the potency of ranolazine to suppress the altered late sodium influx.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of each compound on the atrial electrophysiology cannot be dissected. However, the modes of action of ranolazine and NCX-inhibitors have been investigated before [ 3 , 4 , 13 , 14 ]. Of note, the induction of AF by perfusion with IsoACh does not represent the entire changes in atrial fibrillation and is likely to be associated with intracellular calcium overload [ 25 ], a situation in which NCX-inhibitors are expected to be very effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experimental studies showed that the mechanism of action of ranolazine is not limited to I Na,L and in fact inhibits several key ionic currents (I Na , I Kr , I Ca , I NCX , and I KS ) without changes in I to and I K1 [ 97 ]. Ranolazine has also been found to inhibit TASK-1, an atrial specific potassium channel that is upregulated in AF [ 112 ]. Given that AF at the cellular level is defined by alteration in the expression and function of key ion currents, the observed effects of ranolazine can be mediated by its effects on other currents.…”
Section: I Nal As An Antiarrhythmic Target In Atrial Arrhythmiasmentioning
confidence: 99%